Գլաձորի համալսարանի ուսուցիչները և սաները - Մաթևոսյան, Կարեն
Gladzor University, which operated in the Aghberts‘ Monastery of Vayots‘ Dzor in 1282-1338, was one of the most significant educational, scholarly and cultural centers of medieval Armenia. While Gladzor’s legacy has been well addressed by scholarship, a comprehensive list of the university’s teachers and students is deficient from the literature. This present publication provides such a list, compiled on the basis of available sources. It includes 72 names all told, with corresponding biographical precis drawn from colophons. The article also presents a miniature created in Gladzor in the 1320s, which depicts forty-four figures: the rector of Gladzor University, Esayi, alongside both teachers and students. Гладзорский университет, действовавший в монастыре Ахберц в Вайоц Дзоре в 1282-1338 годах, был одним из важнейших образовательных, научных и культурных центров средневековой Армении. К Гладзору и его наследию обращались многие исследователи, имеется солидное число публикаций, однако полного списка преподавателей и студентов университета по сей день не существовало. В данной публикации этот пробел по возможности восполняется. В список вошло 73 имени, о каждом из которых даны краткие сведения, в основном почерпнутые из памятных записей рукописей. В статье также представлена миниатюра, созданная в Гладзоре в 1320-х годах, на которой изображено 44 человека: ректор Гладзорского университета Есаи Нчеци с преподавателями и учениками.
Keywords: Պատմություն; Հայ կրթօջախներ